Investigating the effect of solvent vapours on crystallinity, phase, and optical, morphological and structural properties of organolead halide perovskite films. Issue 66 (2nd November 2020) - More, Sagar A.; Halor, Rajendra G.; Shaikh, Raees; Bisen, Gauri G.; Tarkas, Hemant S.; Tak, Swapnil R.; Bade, Bharat R.; Jadkar, Sandesh R.; Sali, Jaydeep V.; Ghosh, Sanjay S.
Abstract : Effect of solvent vapours on the micrometer and nanometre scale morphology of CH3 NH3 PbI3 . Abstract : A comprehensive study regarding the effect of different solvent vapours on organolead halide perovskite properties is lacking. In the present work, the impact of exposing CH3 NH3 PbI3 films to the vapours of commonly available solvents has been studied. The interaction with perovskite has been correlated to solvent properties like dielectric constant, molecular dipole moment, Gutmann donor number and boiling point. Changes in the crystallinity, phase, optical absorption, morphologies at both nanometer and micrometer scale, functional groups and structures were studied using X-ray diffraction, UV-visible absorption, FE-SEM, FTIR and Raman spectroscopies. Among the aprotic solvents DMSO and DMF vapours deteriorate the crystallinity, phase, and optical, morphological and structural properties of the perovskite films in a very short time, but due to the difference in solvent property values acetone affects the perovskite properties differently. Polar protic 2-propanol and water vapours moderately affect the perovskite properties. However 2-propanol can solvate the organic cation CH3 NH3 + more efficiently as compared to water and a considerable difference was found in the film properties especially the morphology at the nanoscale. Nonpolar chlorobenzene vapour minutely affects the perovskite morphology but toluene was found to enhance perovskite crystallinity. Solvent properties can be effectively used to interpret the coordination ability of a solvent. The present study can be immensely useful in understanding the effects of different solvent vapours and also their use for post-deposition processing (like solvent vapour annealing) to improve their properties.